2020
DOI: 10.1016/s1473-3099(20)30581-8
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the global epidemiology of COVID-19 from the prepandemic period using web-based surveillance: a cross-sectional analysis

Abstract: Background Scant data are available about global patterns of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spread and global epidemiology of early confirmed cases of COVID-19 outside mainland China. We describe the global spread of SARS-CoV-2 and characteristics of COVID-19 cases and clusters before the characterisation of COVID-19 as a pandemic. Methods Cases of COVID-19 reported between Dec 31, 2019, and March 10, 2020 (ie, the prepandemic period), were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 27 publications
0
62
0
3
Order By: Relevance
“…Consistent with these findings, a Brazilian study reported that 57.5% of 67, 180 cases were males [31]. On the contrary, most of epidemiological reviews and meta-analysis studies reported comparable rates of COVID-19 between males and females, but males tended to have higher fatality and mortality rates than females [5,6,32]. Vulnerability of men for worse outcomes of COVID-19 is probably due to gender-based immunological differences between men and women, and this may impact the woman ability to resist infections including COVID-19 [33].…”
Section: Allele Frequencies Of Abo Blood Groupsmentioning
confidence: 71%
“…Consistent with these findings, a Brazilian study reported that 57.5% of 67, 180 cases were males [31]. On the contrary, most of epidemiological reviews and meta-analysis studies reported comparable rates of COVID-19 between males and females, but males tended to have higher fatality and mortality rates than females [5,6,32]. Vulnerability of men for worse outcomes of COVID-19 is probably due to gender-based immunological differences between men and women, and this may impact the woman ability to resist infections including COVID-19 [33].…”
Section: Allele Frequencies Of Abo Blood Groupsmentioning
confidence: 71%
“…This led to a spreading underdiagnosis of cases and deaths in the region, due to poor testing rates, poor‐quality death certificates, low system integration and political reasons 3 . The fatality rate varies tremendously among countries and is related to different criteria for testing and as a consequence of different levels of underdiagnosis 2,5,30 . In this context, excess deaths could be a useful tool for the overall burden of the pandemics.…”
Section: Covid‐19 In Lamentioning
confidence: 99%
“…While the epidemic started in Asia, the epicenter of the pandemic moved gradually to Europe and North America. During June and July, it expanded into Latin America (LA) 2 . In August, Brazil, Mexico, Peru, Colombia and Chile were among the 10 countries with the most confirmed cases in the world, with still growing numbers.…”
Section: Introductionmentioning
confidence: 99%
“…There is a consensus in the scientific community regarding the possibility of contagion mitigation through the use of face coverings, personal hygiene, and by avoiding crowded and poorly ventilated places [6]. The clusters of infected populations were shown to be more likely in occupational or community settings, lending further credence to the significance of physical distancing [7]. The white collar jobs are relying on workfrom-home and virtual communication, while the blue collar workers are being advised to abide by the 6 feet distance rule.…”
Section: Introductionmentioning
confidence: 99%